1980
DOI: 10.5962/bhl.title.135540
|View full text |Cite
|
Sign up to set email alerts
|

Sphagnaceae (peat moss family) of New York State

Abstract: For all illustrations in this publication the following letter designations apply:A. Habit sketch B. Branch leaf from spreading branch C. Transverse section of branch leaf from spreading branch D. Convex surface, upper middle region, of branch leaf from spreading branch DM. Same as D but middle region DL. Same as D but lower middle region E. Concave surface, upper middle region, of branch leaf from spreading branch EM. Same as E but middle region EL. Same as E but lower middle region F. Apex of spreading branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 3 publications
1
68
0
Order By: Relevance
“…in North America which has a broad distribution in the Northern Hemisphere. Sphagnum angustifolium is also very common in open, poor to medium fen peatlands (Andrus 1980), but it is also widespread in poor to medium-wooded coniferous fens and cedar swamps.…”
Section: S Aureummentioning
confidence: 99%
See 1 more Smart Citation
“…in North America which has a broad distribution in the Northern Hemisphere. Sphagnum angustifolium is also very common in open, poor to medium fen peatlands (Andrus 1980), but it is also widespread in poor to medium-wooded coniferous fens and cedar swamps.…”
Section: S Aureummentioning
confidence: 99%
“…The nearest populations outside of Costa Rica are in the southwestern United States, but Karlin believed that is probably occurs at other high elevation habitats in Central America. The site at which it is found on Cerro de la Muerte is typical of the intermediate fens and minerotrophic habitats in which it occurs in North America (Andrus 1980, Crum 1984.…”
Section: S Aureummentioning
confidence: 99%
“…In the latter study, production of red pigment could be induced by cool nights (12 h, O.s°C) and warm days (12 h, 18°C). Production of red pigments in many species of Sphagna is a characteristic and taxonomically important character, but with those species pigment production is a response to ecological conditions (Andrus, 1980). Other bryophytes almost always have red coloration (e.g.…”
Section: Michigan Technological Universitymentioning
confidence: 99%
“…It is known that climate affects the development of peatland forms (Sjtrs 1948;Eurola 1962;Moore and Bellamy 1974;Damman 1977Damman , 1979, and taxonomic species descriptions often include a geographical limit based upon climate (Vitt and Andrus 1977;Andrus 1980;Janssens 1983). Recently, it has been demonstrated that climate affects the distribution and abundance of bryophytes along an east-west climatic gradient in western Canada (Gignac and Vitt 1990;Gignac et al 1991) and along a temperature gradient for vascular plant species in eastern ombrotrophic bogs (Glaser and Foster 1984;Glaser 1992).…”
Section: Introductionmentioning
confidence: 99%